Religion and conflict in modern South Asia - Gould, William 1973- (Cambridge University Press, 2012)
"This is an incisive analysis of religious conflict in South Asia, which, the author contends, arises out of the weakness of political and state structures rather than the clash of civilizations"--Provided by publisher.